Behind the Colors of Synesthesia - Halim, Angeline Freshbi Chesa; Fahira, Zihan; Lamanepa, Rosalia Katarina; Pikoli, Amr Yazid; Wimbrawati, Supra; Kusrohmaniah, Sri (Pena Medika : Jurnal Kesehatan, 2024)
Synesthesia is a neurological phenomenon that affects perception, in which stimuli are affected by one thing (such as letters and numbers), thus generating unusual secondary sensory experiences such as color. Purpose of the research is to know the mechanisms of synesthesia in the body. Method for hypothesis testing with the cross-activation, cortical disinhibition, and the re-entrant feedback theory. A person who experiences synesthesia has an extraordinary mentality because they can see the color of sounds, numbers can be colored, and words can have taste. Synesthesia affects an individual's perception and experience in everyday life. This impacts their interaction with the environment and their understanding of sensory information, potentially affecting the allocation of attention. A common hypothesis states synesthesia arises due to excessive neural connections between cortical regions. Synesthesia can have a significant impact on an individual's visual perception and abilities, leading to unique experiences and potentially enhancing the processing of certain visual information in eve